Segmentation techniques for morphometric measurements of blood cells: Overview and research challenges. (December 2022) - Ahmed, Imran; Balestrieri, Eulalia; Tudosa, Ioan; Lamonaca, Francesco
Abstract: Measurement of Morphological Blood Cell Parameter (MBCP) plays a key role in hematological examination and diagnosis of various diseases. Recently, Cellular Image Analysis (CIA) techniques have been widely used in clinical diagnosis. Nowadays, these CIA techniques are mainly based on image acquisition followed by digital processing for image segmentation and measurement of MBCP. This paper presents an overview of segmentation methods currently used for measurement of MBCP. Furthermore, main challenges and limitations related to metrological aspects that can affect the performances of these methods are also highlighted.